About thermodynamic evolution of Еarth crust and tectonic plates - R.Ya. Belevtsev; V.I. Blajko; S.I. Terechenko (Геофизический журнал, 2016)
Based on thermodynamic analysis of the geological structure, PT conditions on the earth's surface, and the powers that cause tectonic drift of continental and oceanic plates, presented physical and chemical regularity  of evolution geospheres. These mainly related to the space powers of the Earth rotation around its axis, by gravity powers of plates by the Earth, Sun and Moon, as well as between neighbors  plates. In  equatorial latitudes the rotational power is maximal  and shift plates toward the equator. The most stable continent is Africa, which is associated with the maximum gravity to the Sun at perihelion elliptical orbit of the Earth. So,  the drift of plates on the Earth's surface comes from Africa to the Pacific Ocean. Plate tectonics is primarily dependent on the plasticity of their base, which were magmatic in Archean and since Phanerozoic cooled with the formation plastic talc-serpentine soles. Due to which activated mobilism of plate. To the borders confined earthquake plates, which indicate the latter. Moving sedimentation zone during evolution transformed into folding system, which is much smaller in area, which is also indicate  of plate tectonics. Oceanic plates have a small power, but significant temperature graditent, because in them since Mesozoic from ultramafic mantle melted basalt magma, which contributes to oceanic plates drift on the base of the magma and the continental plates on the talc-serpentine soles  from  the mid-ocean rifts. So open up the Atlantic and Indian oceans, and closes the Pacific. On Mars, we have been active in the Precambrian moving plates like Earth, which are mainly located in the equatorial zone, including the plate in the South pole